Diversity and Abundance of Beetle (Coleoptera) Functional Groups in a Range of Land Use System in Jambi, Sumatra (Biodiversitas Journal of Biological Diversity, 2009)
Degradation of tropical rain forest might exert impacts on biodiversity loss and affect the function and stability of the related ecosystems. The objective of this study was to study the impact of land use systems (LUS) on the diversity and abundance of beetle functional groups in Jambi area, Sumatra. This research was carried out during the rainy season (May-June) of 2004. Inventory and collection of beetles have been conducted using winkler method across six land use systems, i.e. primary forest, secondary forest, Imperata grassland, rubber plantation, oilpalm plantation, and cassava garden. The result showed that a total of 47 families and subfamilies of beetles was found in the study area, and they were classified into four major functional groups, i.e. herbivore, predator, scavenger, and fungivore. There were apparent changes in proportion, diversity, and abundance of beetle functional groups from forests to other land use systems. The bulk of beetle diversity and abundance appeared to converge in primary forest and secondary forest and predatory beetles were the most diverse and the most abundant of the four major functional groups.Key words: beetle, land use system, diversity, abundance, Sumatra.